Optimization of Direct Sales and Sales Canvasser Sales Target Monitoring With RESTful API Implementation on Web-Based Monitoring System - Friwaldi, Restian Dwi; Widiono, Suyud (Journal of Applied Informatics and Computing, 2024)
RESTful API offers advantages in real-time data exchange, scalability, and ease of integration with other systems. This research aims to develop a web-based monitoring system using RESTful API to optimise the monitoring of direct sales targets and sales canvassers at. This system is built with Laravel framework and Agile method, focusing on ease of use and real-time data access. Tests were conducted using Apache JMeter with load scenarios of 500, 750, and 1000 users. The test results showed response times of 758 ms for 500 users, 762 ms for 750 users, and 880 ms for 1000 users, all below the target of 900 ms. The error rate was recorded at 0.00%, indicating the high reliability of the system. The throughput achieved was 90.30 requests per second for 500 users, 124.30 requests per second for 750 users, and 159.10 requests per second for 1000 users, exceeding the target of 150 requests per second. Recommendations for further development are the integration of mobile applications for accessibility and real-time monitoring of sales performance.